HUBUNGAN ANTARA SELF ESTEEM DENGAN PENYESUAIAN DIRI PADA SISWA TAHUN PERTAMA SMA KRISTA MITRA SEMARANG - Timorora Sandha; Sri Hartati; Nailul Fauziah (Jurnal EMPATI, 2012)
Adjustment can be achieved through a learning process to understand, know, and try to do what individual and their environment wants. The first year students will be faced with adjustment problem. One of the factor that affect it is self esteem. This study aims to find empirically the correlation between self esteem and adjustment un the first year student at Krista Mitra High School Semarang.This study population was Tenth Graders of Krista Mitra High School Semarang with samples as many as 73 students. The sampling technique used cluster random sampling technique. The data collection method in this study used the psychological scale that was a Adjustment Scale that consisting of 50 valid items and Self Esteem Scale that consists of 38 valid items. Data analysis used simple regression technique.The results of study indicate that the correlation coefficient (rxy) = 0,740 with significance level (p) of 0,000 (p<0,01). It means that the hypothesis in this study has accepted. The direction of the correlation is positive, which means that the higher self esteem, the higher adjustment, and vice versa, the lower self esteem, the lower adjustment. The effective contribution of self esteem is 54,8% toward the adjustment, which means that there are 45,2% og other factors that affect the adjustment is not revealed in this study